1991
DOI: 10.1021/j100164a054
|View full text |Cite
|
Sign up to set email alerts
|

A reexamination of the chemisorption of trimethylaluminum on silica

Abstract: Fourier transform infrared spectroscopy, temperature-programmed desorption, and X-ray photoelectron spectroscopy have been used to study the chemisorption and decomposition of trimethylaluminum (TMA) on silica under high vacuum. By annealing a series of silica substrates from 425 to 1573 K prior to TMA exposures at 300 K, we have examined the distributions of chemisorption products as a function of the relative concentrations of isolated hydroxyls (OHi), hydrogen-bonded hydroxyls (OHH), and siloxane bridges. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 0 publications
11
111
1
1
Order By: Relevance
“…Coordination of 6 to a nearby siloxane oxygen is likely to occur in order to maintain the preferred tetracoordination at Al. This hypothesis is nevertheless consistent with the ability of AlMe 3 /silica to adsorb Lewis bases such as Et 2 O [47] and NH 3 [43,51]. Adsorption may occur by displacement of the coordinated siloxane oxygen atom, instead of being interpreted as evidence for persistent threecoordinate Al sites [47].…”
Section: Proposed Structure Of Alme 3 /Silicasupporting
confidence: 74%
See 2 more Smart Citations
“…Coordination of 6 to a nearby siloxane oxygen is likely to occur in order to maintain the preferred tetracoordination at Al. This hypothesis is nevertheless consistent with the ability of AlMe 3 /silica to adsorb Lewis bases such as Et 2 O [47] and NH 3 [43,51]. Adsorption may occur by displacement of the coordinated siloxane oxygen atom, instead of being interpreted as evidence for persistent threecoordinate Al sites [47].…”
Section: Proposed Structure Of Alme 3 /Silicasupporting
confidence: 74%
“…Regardless of the origin of the silica, chemisorption was suggested to involve formation of isolated three-coordinate methylaluminum and dimethylaluminum sites, associated with O or Si atoms of the surface, Scheme 2. Four-coordinate Al sites, described as physisorbed, were assumed to appear only when silica is oversaturated with AlMe 3 [45,47].…”
Section: The Cocatalyst/support Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very low levels of metal detected on 600ЊC/HMDS silica gel for all the reactants studied suggest that none react with siloxane bonds. Previous work (20,21) has shown that only the most reactive reagents, such as aluminum alkyls, react with siloxanes under similar conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous work on metallocenes heterogenization onto SiO 2 surfaces offers both theoretical and experimental confirmation of this mechanism. 23,24 Additional evidence comes from the FTIR spectrum of E-glass (which contains ϳ14% Al 2 O 3 in its formulation). As shown in Figure 18c, the bands assigned to AlOOOSi and AlOO vibrations are also present.…”
Section: Mao Pretreated Fibersmentioning
confidence: 99%